A New Multi-tree and Dual Index based Firewall Optimization Algorithm - Cuixia Ni; Guang Jin; Xianliang Jiang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Using statistical analysis strategy, a large-scale firewall log files is analyzed and two main characteristics, the protocol field and the IP address field, is extracted in this paper. Based on the extracted features and the characteristics of multi-tree and dual-index strategy, we design a better firewall optimization algorithm. Compared with the Stochastic Distribution Multibit-trie (SDMTrie) algorithm, our proposed algorithm can greatly decrease the preprocessing time and improve the searching and filtering process. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2465